Modified null space strategy to solve consensus problem - Aman Sharma; Naga G. Kurapati; Ravi Prasad K. Jagannath; Patrice Wira; Shyam Lal; Adapa V. Narasimhadhan (Kuwait Journal of Science)
In the domain of multi robot systems, there are several applicationswhere agreement of all the individual robots at a point, also known as con-sensus point or Rendezvous point, is desired. To facilitate this agreement,a control system needs to be designed. In this paper, the performanceaspect of null space based control strategy to solve consensus problem,in a complex environment, is evaluated both theoretically as well as bymeans of extensive simulation studies. Initially, performance of null spacestrategy will be tested for a single mobile robot and outcomes will thenbe then extended for a multi robot system. The performance is testedfor robots navigating in an environment consisting of rectangular andconcave shaped obstacles. In order to solve the consensus problem, anon-hierarchical projection based null space strategy, which will be re-ferred to as modied null space based strategy is also proposed. Finally, acomparative analysis will be presented to contrast the dierences betweenthe conventional null space based strategy and the proposed modied nullspace control strategy.